EFEKTIVITAS MODEL PEMBELAJARAN NHT DENGAN TPS UNTUK MENINGKATKAN BERPIKIR KRITIS DAN HASIL BELAJAR MATERI KEBERAGAMAN DI SEKOLAH DASAR - Kusumawati, Linda; Indarini, Endang (Universitas Muria Kudus, 2024)
The aim of this research is to determine the effectiveness of the Numbered Heads Together (NHT) model compared to the Think Pair Share (TPS) model in improving critical thinking skills and learning outcomes on the subject of diversity in elementary school. The research method used in this study is a quasi-experimental design with a Nonequivalent Control Group Design. The data analysis results indicate that there is a difference in the effectiveness of the Think Pair Share (TPS) learning model in enhancing critical thinking skills and learning outcomes on the subject of diversity for fourth-grade students in elementary school.The research obtained data from two research samples, with the average post-test scores of the experimental group 2, which was given the Think Pair Share (TPS) learning model treatment, being 82.84, higher than the average post-test scores of the experimental group 1, which was given the Numbered Heads Together (NHT) learning model treatment, which was 72.06. Thus, it can be concluded that the students' scores with the Think Pair Share (TPS) learning model are higher than those with the Numbered Heads Together (NHT) learning model. This is evident from the difference in the average post-test scores of the students, with the t-test results showing t-calculated t-table, i.e., 4.198 2.048.